Nota de la editora - Melinda Dooly (Universitat Autònoma de Barcelona, 2013)
Our last volume of this year 2013 offers an interesting array of topics and approaches to language and literature teaching and learning. Our guest author, Dr. Selim Ben Said of the National Institute of Education of Singapore explores the mediation of identity during the process of becoming a language teacher. ...